RelaxDHT: a Churn-Resilient Replication Strategy for Peer-to-Peer Distributed Hash-Tables - Legtchenko, Sergey; Monnet, Sébastien; Sens, Pierre; Muller, Gilles (ACM Transactions on Autonomous and Adaptive Systems (TAAS), 2012)
DHT-based P2P systems provide a fault-tolerant and scalable means to store data blocks in a fully distributed way. Unfortunately, recent studies have shown that if connection/disconnection frequency is too high, data blocks may be lost. This is true for most of the current DHT-based system's implementations. To deal with this problem, it is necessary to build more efficient replication and maintenance mechanisms. In this paper, we study the effect of churn on PAST, an existing DHT-based P2P system. We then propose solutions to enhance churn tolerance and evaluate them through discrete event simulation.